Skrining Fitokimia, Formulasi, dan Karakteristik Fisik Sediaan Soothing Gel Daging Daun Lidah Buaya (Aloe vera (L.) Burm.f.) - Sinaga, Rosalinda Mahdalena; Lubis, Minda Sari; Dalimunthe, Gabena Indrayani; Rahayu, Yayuk Putri (Jurnal Farmasi & Sains Indonesia, 2023)
Aloe vera (Aloe vera (L.) Burm.f.) can make the skin not dry quickly and feel moisturised. Soothing gel works effectively to restore skin moisture, provide comfort and a cooling effect on red and irritated skin so that the skin condition returns to normal, and prevents skin dryness. The aim of the study was to determine the various secondary metabolites in aloe vera leaf extract to determine differences in concentrations of aloe vera leaf extract in soothing gel preparations on the physical characteristics of the preparations and to determine physical changes before and after stability tests were carried out using the cycling test method. The research method was used experimental, with the independent variables varying the concentration of aloe vera leaf extract 0% (blank), 1%, 2%, and 3%, the dependent variable secondary metabolites and physical characteristics. The sample preparation method is wet sorting and other methods used are phytochemical screening, viscometry, and cycling tests. The results of the phytochemical screening showed that aloe vera leaf extract contains secondary metabolites of flavonoids, glycosides, tannins, saponins, and steroids.